2019
DOI: 10.1016/j.ijpharm.2018.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Protecting bactofencin A to enable its antimicrobial activity using mesoporous matrices

Abstract: There is huge global concern surrounding the emergence of antimicrobial resistant bacteria and this is resulting in an inability to treat infectious diseases. This is due to a lack of new antimicrobials coming to the market and irresponsible use of traditional antibiotics. Bactofencin A, a novel antimicrobial peptide which shows potential as an antibiotic, is susceptible to enzyme degradation. To improve its solution stability and inherent activity, bactofencin A was loaded onto a traditional silica mesoporous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…The incorporation of bacteriocin-producing probiotics into foods and feeds and assuring their activity during processing and subsequent passage through the host's gastrointestinal tract is a challenge that is being addressed through the discovery and development of new bacteriocin producing strains and novel encapsulation techniques [58][59][60]62 . Commercial scale bacteriocin production is still hampered by high costs and low peptide yield but cost efficiency is being improved through optimisation of fermentation processes and bioengineering strains for maximum production of bacteriocins 63 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of bacteriocin-producing probiotics into foods and feeds and assuring their activity during processing and subsequent passage through the host's gastrointestinal tract is a challenge that is being addressed through the discovery and development of new bacteriocin producing strains and novel encapsulation techniques [58][59][60]62 . Commercial scale bacteriocin production is still hampered by high costs and low peptide yield but cost efficiency is being improved through optimisation of fermentation processes and bioengineering strains for maximum production of bacteriocins 63 .…”
Section: Discussionmentioning
confidence: 99%
“…One of the challenges for bacteriocins in feed applications is the ability to pass through the gastrointestinal tract without digestion by proteolytic enzymes and this can be achieved through encapsulation, a protective technique that ensures successful delivery to the target site without loss of bioactivity where they can be released in a controlled fashion 20 . Both nisin A and bactofencin A were recently successfully encapsulated in mesoporous matrices with nisin A being protected from degradation by pepsin and bactofencin A from trypsin 58,59 . Bioactive intact nisin and nisin fractions were detected in the faeces of mice pellets following feeding with nisin encapsulated in starch based matrices therefore achieving the aim of delivering intact nisin to the gut by oral means 60 .…”
Section: Bacteriocin Producing Probiotic Cultures As Antimicrobials In Animal Feedmentioning
confidence: 99%
“…The obtained drug delivery system exhibited bioavailability toward HaCaT keratinocytes and a higher accumulation of formulated drug in comparison with free methotrexate. Report [195] was dedicated to the encapsulation of peptide bactofencin A in SBA-15 type mesoporous silica nanoparticles. Encapsulated drug demonstrated superior antibacterial properties in comparison with free drug and was capable to suppress the growth of Staphylococcus aureus bacteria by ~80%.…”
Section: Mesoporous Silica Nanoparticles (Msn) As Perspective Vehicles Of New Generation For Drug Deliverymentioning
confidence: 99%
“…Along this line, in an very recent example by us, we demonstrated the antibacterial effects of the concanavalin A (ConA) protein in combination with levofloxacin, a typical antibiotic. 59 In this example, to combine both antibiotic species we employed carboxylate-modified MSNs, which were loaded with levofloxacin and functionalized with ConA upon drug loading. The effect of this dual-action nanosystem permitted us to achieve a complete destruction of the E. coli biofilm even at minimal concentrations (10 μg MSNs per mL), improving any of the precedent models and showing that combination therapy usually improves treatments with single-drug delivery systems.…”
Section: Delivery Of Antibiotic Compoundsmentioning
confidence: 99%
“…In addition, in a contribution by Durack et al bactofencin A also demonstrated an interesting antibiotic effect when loaded into mesoporous matrices. 59 In this work the authors evaluated the performance of such protein when loaded into SBA-15 porous solids against S. aureus . Unfortunately, in this case the absence of gated pores permitted a fast diffusion of protein that led to an almost complete release within five hours, which prevented a long-lasting effect as the OD of bacterial culture was recovered quickly.…”
Section: Delivery Of Antibiotic Compoundsmentioning
confidence: 99%